Comparative issues in public sector unionism the United States and the Philippines - Ramos, Elias T. (1987)
In the Philippines' search for a viable model of unionism in the public sector, some lessons from the US experience can be drawn despite the wide disparities in economic, political, social, cultural, and historic conditions prevailing in these two countries. Rapid growth of employment in the public sector, the gradual erosion of the distinction between private and public sector employment, and determining what is an essential service in government and who is the public employer, are vital issues that must be addressed to ensure a lasting industrial peace in the public sector.
Keywords: Labor unions; Labor unions -- Government policy; Labor unions -- United States